Open Sources 2.0 the continuing evolution - DiBona, Chris (O'Reilly, 2005)
Open Sources 2.0 is a collection of insightful and thought-provoking essays from today's technology leaders that continues painting the evolutionary picture that developed in the 1999 book Open Sources: Voices from the Revolution .These essays explore open source's impact on the software industry and reveal how open source concepts are infiltrating other areas of commerce and society. The essays appeal to a broad audience: the software developer will find thoughtful reflections on practices and methodology from leading open source developers like Jeremy Allison and Ben Laurie, while the busine.
Includes bibliographical references. - Print version record
Keywords: Open source software; Logiciels libres; REFERENCE; General